Association between presence of the metabolic syndrome and its components with carotid intima-media thickness and carotid and femoral plaque area: a population study - Panayiotou, Andrie G.; Griffin, Maura B.; Tyllis, Theodosis H.; Georgiou, Niki; Bond, Dawn; Nicolaides, Andrew N.; Kouis, Panayiotis (My University, 2013)
Abstract. Background: We aimed to explore the association between presence and number of components of the Metabolic Syndrome (MetS) and subclinical atherosclerosis outcomes (common carotid intima media thickness, plaque presence and sum of plaque area) in both the carotid and femoral bifurcations. Methods. Cross-sectional analysis of 771 volunteers from the ongoing epidemiological Cyprus Study (46% male; mean age = 60.1 ± 9.8). (a) Carotid intima-media thickness (IMTcc), (b) sum of plaque area in the carotid bifurcations (sum of the largest plaques in each carotid bifurcation-SPAcar), (c) sum of plaque area in the femoral bifurcations (sum of the largest plaques in each femoral bifurcation-SPAfem) and (d) sum of plaque area in both carotid and femoral bifurcations (sum of the areas of the largest plaques present in each of the four bifurcations-SPA) were measured at baseline using ultrasound. Presence and number of components of the MetS was ascertained using the National Cholesterol Education Program ATPIII definition and their association tested using multivariable regression models. Results: MetS was present in 259 (33.6%) individuals and was associated with a 0.02 mm increase in IMTcc (95% CI: 0.00 to 0.04, p = 0.047) after adjustment for age, sex, family history of CVD, alcohol consumption (BU/week) and smoking (pack-years). Each additional component of the MetS was associated with a 16% higher SPA (95% CI: 6.8% to 25.2%, p§ssub§for trend§esub§ = 0.001), a 10% higher SPAcar (95% CI: 5% to 24%, p§ssub§for trend§esub§ = 0.003) and a 14% higher SPAfem in the adjusted model. Conclusions: We confirm an association between the MetS and IMTcc as well as report for the first time an association between the MetS and its components and femoral plaque area, in a general population over 40 years of age. Having any risk factors for the MetS increases the risk for subclinical atherosclerosis, with the risk increasing with each additional component. Using the dichotomous definition of the MetS may be overlooking the risk for subclinical atherosclerosis -and by inference future cardiovascular events- associated with having less than 3 risk factors.
Keywords: Atherosclerotic plaques; Carotid; Femoral; IMT; Metabolic syndrome; Metabolic syndrome components; Plaque area